Structural and mechanical characterization of bioresorbable, elastomeric nanocomposites from poly(glycerol sebacate)/nanohydroxyapatite for tissue transport applications. Issue 7 (22nd July 2015) - Rosenbalm, Tabitha N.; Teruel, Maria; Day, Cynthia S.; Donati, George L.; Morykwas, Michael; Argenta, Louis; Kuthirummal, Narayanan; Levi‐Polyachenko, Nicole
Abstract: Poly(glycerol sebacate) (PGS)/nanohydroxyapatite (nHA) composites were assessed to develop new materials for closure via tissue transport for nonhealing defects (e.g., cleft palate and large skin wounds). The elastic shape memory polymer, PGS, was reinforced with nHA at 3 and 5% loading to increase the mechanical properties compared with the undoped PGS. Differential scanning calorimetry (DSC) was utilized to identify a glass transition temperature ( T g ) of −25°C. X‐ray diffraction demonstrated a reduction in the amorphous nature of the material. The Fourier transform infrared photoacoustic spectral (FTIR‐PAS) data showed decreased CO bonding and increased hydrogen bonding with increased nHA incorporation. Composites exhibited Young's moduli in the range of 0.25–0.5 MPa and tensile strength of 1.5–3 N. No significant difference in extension to break (∼50 mm) with addition of nHA was observed. The elastic modulus significantly increased for 5% PGS/nHA compared to 0 and 3% PGS/nHA and tensile strength significantly increased for 3% PGS/nHA compared to 0 and 5% PGS/nHA. Degradation of 5% nHA/PGS significantly increased during the second week compared to PGS 0 and 3% PGS/nHA. The accelerated degradation for 5% PGS/nHA coupled with decreased flexibility and tensile strength implies an interruption in crosslinking. By maintaining flexibility and extension while increasing tensile strength, the 3% PGS/nHA doped satisfied the force range desired for closure of soft tissue defects. Based on this work, PGS with 3% nHA shape memory polymers should serve as a good candidate for closure of nonhealing soft tissues. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 104B: 1366–1373, 2016.